PENGARUH PENDIDIKAN KESEHATAN DENGAN MIXED MEDIA EDUCATION INTERVENTION PROGRAM TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG ANEMIA GIZI BESI - Syeptri Agiani Putri; Meri Neherta; Lili Fajria (Jurnal Ners Indonesia, 2023)
Anemia is one of the health problems that currently occurs in female adolescents. The intervention strategy in managing anemia is not only by giving iron supplements but also can be prevented by providing proper knowledge about healthy diets, and lifestyle changes and informing the adverse effects of iron deficiencies. The purpose of this research was to determine the effects of health education with a mixed media education intervention program on the knowledge and attitude of female adolescents about iron nutritional anemia at Senior High School number 1 of Talamau. The research design was quasi-experimental with a pre-post test with a control group. The 190 sample was taken by using a proportionate stratified random sampling technique and divided equally into intervention and control groups. The research instruments used in this research were valid and reliable knowledge and attitude questionnaires. The results with paired sample T-tests showed that there is an influence of the health education intervention program with the mixed media education intervention on the knowledge (p-value 0.000) and attitude (p-value 0.000) of female adolescents about iron nutritional anemia. It is recommended that Talu Community Health Center workers make the mixed media education intervention program (PowerPoint lectures, video motions, and demonstrations) one of the health education media in an effort to improve the knowledge and attitude of adolescent females related to iron nutritional anemia.